2003
DOI: 10.1172/jci18921
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein: a critical update

Abstract: IntroductionIn the mid 1990s, immunoassays for C-reactive protein (CRP), with greater sensitivity than those previously in routine use, revealed that increased CRP values, even within the range previously considered normal, strongly predict future coronary events. These findings triggered widespread interest, especially, remarkably, in the US, where the clinical use of CRP measurement had been largely ignored for about 30 years. CRP production is part of the nonspecific acute-phase response to most forms of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
1,055
8
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,575 publications
(1,100 citation statements)
references
References 59 publications
(31 reference statements)
25
1,055
8
12
Order By: Relevance
“…Moreover, PTX3 production is stimulated by several proinflammatory cytokines, such as IL1b, TNFa and IL10, and by TLR-agonists and oxidised LDL, but not by IL6 (26). Conversely, the latter is the most potent activator of CRP secretion (4). In addition, in several studies carried out in different conditions, the correlation between PTX3 and CRP levels was weak or even absent (9,27,28).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, PTX3 production is stimulated by several proinflammatory cytokines, such as IL1b, TNFa and IL10, and by TLR-agonists and oxidised LDL, but not by IL6 (26). Conversely, the latter is the most potent activator of CRP secretion (4). In addition, in several studies carried out in different conditions, the correlation between PTX3 and CRP levels was weak or even absent (9,27,28).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…It belongs to the pentraxin superfamily and is one of the best characterised biomarkers of low-grade chronic inflammation, a key process in the pathogenesis of atherosclerosis (4). Several epidemiological studies, both in subjects with increased cardiovascular risk and in the general population, have shown that serum CRP independently predicts cardiovascular events (5).…”
Section: Introductionmentioning
confidence: 99%
“…CRP is a nonspecific acute phase reactant that rapidly increases in plasma concentration in response to inflammation, infection, and injury (Pepys & Hirschfeld, 2003 linked minor CRP elevations, previously considered clinically normal, with increased cardiovascular risk (Ridker et al, 1998). Elevated levels of CRP are linked to factors such as obesity (Rexrode et al, 2003), and with several dimensions of psychosocial stress, including lack of social integration (Ford et al, 2006) and low SES (Nazmi & Victora, 2007).…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…The prognostic impact of CRP has also been demonstrated in a range of other malignancies [23,24,25,26,27,28,29,30]. CRP is an acute-phase reactant and a sensitive, albeit non-specific, marker of tissue damage and inflammation which have established roles in carcinogenesis [31,32,33]. Pro-inflammatory cytokines released from the tumor microenvironment induce CRP synthesis by the liver [34].…”
Section: Discussionmentioning
confidence: 99%